Safeguarding spouses' personal non-property rights in European Court of Human Rights jurisprudence - Vatras, Volodymyr; Oksaniuk, Oleh; Sabluk, Serhii; Havrik, Roman; Vasylieva-Shalamova, Zhanna (Edelweiss Applied Science and Technology, 2025)
The protection of personal non-property rights is important for the state because it demonstrates the ability to protect the rights and interests of individuals. The research aims to study the peculiarities of the protection of the non-property rights of spouses based on the guarantee of their inalienable rights, such as the right to parenthood, personal development, prohibition of discrimination, and respect for honor and dignity. The relevance of this topic is connected with the need to protect these rights in the international human rights body - the ECHR. The study uses methods of analysis and synthesis of scientific approaches to the protection of non-property rights of spouses, as well as consideration of case law from the European Court of Human Rights (ECHR). The legislation of different countries and the peculiarities of court proceedings are analyzed. The main conclusions of the study show that the protection of non-property rights of spouses plays a key role in family law. The ECtHR, when considering cases, is guided by the Convention, which guarantees respect for private and family life. The European Court recognizes human rights as the supreme value, which is confirmed by its decisions in favor of the protection of non-property rights. Thus, the protection of non-property rights of spouses is an important category of family law that requires careful scrutiny and immediate resolution. The ECHR recommendations aimed at improving the legal framework and ensuring transparency are of great importance for Ukraine's integration into international legal standards and the protection of citizens' rights.